Трансформація інструментів традиційного комплексу маркетингу в електронному бізнесі - Девиченко, Анастасія Михайлівна; Кобєлєв, Валерій Миколайович (НТУ "ХПІ", 2017)
В роботі виконано аналіз відмінностей в структурі комплексу інтернет-маркетингу, де відображені зміни пріоритету інструментів інтернет-маркетингу в порівнянні з традиційним комплексом маркетингу. Одним з основних властивостей середовища Інтернет є його гіпермедійна природа, яка характеризується високою ефективністю в поданні та засвоєнні інформації, що значно підвищує можливості маркетингу для посилення взаємозв'язку підприємств і споживачів.

The article analyzes the differences in the structure of the internet-marketing complex, which reflects the changes in the priority of internet-marketing tools in comparison with the traditional marketing complex. Internet-marketing is the practical use of all aspects of traditional marketing on the Internet, affecting the main elements of the marketing mix: price, product, place of sales and promotion. It has the same structure as traditional marketing, but operates at a qualitatively different level of economic relations. One of the main properties of the Internet environment is its hypermedia nature, which is characterized by high efficiency in the presentation and assimilation of information, which greatly expands marketing opportunities to improve the interconnection of enterprises and consumers. The task for the near future is further institutionalization of the relations that have developed in the framework of electronic business, and the formation of a special theory of internet-marketing that reflects its features and priorities.
Transformation of the traditional tools of the marketing mix in e-business
Keywords: електронна комерція; інтернет-маркетинг; традиційний маркетинг; маркетингові комунікації; збутова політика; товарна політика; комунікативна політика; реклама; мережа Інтернет; e-commerce; internet-marketing; traditional marketing; sales policy; product policy; marketing communications; advertising; Internet